A influência dos estilos de liderança no engajamento da equipe mediada pelo senso de pertencimento das pessoas em gestão de projetos - Silva Júnior, Osmar da (2020)
Traditionally, there is a distinction between management and leadership roles in organizations and the discussions created contemplate management and leadership as synonyms in some cases. In this context, within the project management environment, it is studied how leadership can directly impact project results. However, these concepts are different and many studies still address leadership in the purely technical aspect, where the project manager would be a problem solver and efficiently operate tasks. Thus, these studies disregard the leadership that arises through behavior, taking into account leadership that is acquired by the formal position exercised. However, it is the behavioral aspects of leadership that contribute to the competence of individuals and groups, because if the project manager is able to influence the behavior of a team and achieve the goals, that person is considered a leader. Thus, the leader must not only emerge as a hierarchical position and technical aspects, but must be forged in his behaviors and leadership skills. Project managers increasingly need to learn to develop the power of leadership, and through leadership style, influence subordinates by stimulating a sense of belonging, which generates people's engagement. Based on this context, this study aims to assess the influence of the leadership styles of project managers on engagement mediated by people's sense of belonging in project management. To this end, the Systematic Literature Review method from the Web of Science database was initially used. In this stage, 113 articles were found that were refined in a screening process that resulted in 53 articles. The articles were analyzed and categorized in a spreadsheet by types of leadership, the data was consolidated making a critical discussion about this content. Research has been identified that has been developed in order to determine the leadership styles and engagement related to the project's success, however, there is a lack of studies that tested and validated scales of the construct sense of belonging in projects. In the second phase of this research, validated sense of belonging scales from other areas of study were tested in order to contribute to project management research. Thus, an electronic questionnaire was distributed online to project management professionals who participated in projects in various segments. Confirmatory factor analysis techniques and structural equation modeling were used, which were performed using IBM® SPSS® Amos 18.0 software. The results point to a significant direct relationship between leadership and engagement mediated by the sense of belonging. It became evident to us that transformational leadership is the leadership style that promotes greater engagement, whereas the sense of belonging has a strong influence on this relationship, with a total mediation effect. The results of RSL and empirical data suggest that leadership is not in office, it is in the acceptance or legitimacy that its followers perceive for social behavior. In addition, the leadership style can influence people and their emotions in conducting projects, through the engagement generated by the sense of belonging. The results of the structural model confirmed that there is a direct relationship between leadership and engagement and the sense of belonging, and also, we confirm that the sense of belonging mediates the relationship of the leadership and the engagement of the project team. With this, we prove that transformational leadership is the leadership style that promotes greater engagement, insofar as, the sense of belonging has a strong influence on this relationship, with total mediation effect.